The Interaction of Hydroxymandelate Synthase with the 4-Hydroxyphenylpyruvate Dioxygenase Inhibitor: NTBC - Conrad, John A. (2008)
Hydroxymandelate synthase (HMS) catalyzes the committed step in the formation of para-hydroxyphenylglycine, a recurrent substructure of polycyclic non-ribosomal peptide antibiotics such as vancomycin. HMS uses the same substrates as 4-hydroxyphenylpyruvate dioxygenase (HPPD), 4-hydroxyphenylpyruvate (HPP) and O(2), and also conducts a dioxygenation reaction. The difference between the two lies in the insertion of the second oxygen atom, HMS directing this atom onto the benzylic carbon of the substrate while HPPD hydroxylates the aromatic C1 carbon. We have shown that HMS will bind NTBC, a herbicide/therapeutic whose mode of action is based on the inhibition of HPPD. This occurs despite the difference in residues at the active site of HMS from those known to contact the inhibitor in HPPD. Moreover, the minimal kinetic mechanism for association of NTBC to HMS differs only slightly from that observed with HPPD. The primary difference is that three charge-transfer species are observed to accumulate during association. The first reversible complex forms with a weak dissociation constant of 520 µM, the subsequent two charge-transfer complexes form with rate constants of 2.7 s(−1) and 0.67 s(−1). As was the case for HPPD, the final complex has the most intense charge-transfer, is not observed to dissociate, and is unreactive towards dioxygen.